Kajian Teologis tentang Budaya Mopat Asam Dayak Kebahant dan Relevansinya bagi Persembahan Kandungan Kristen - Jeprianus; Budiman, Sabda (Jurnal Teologi Kontekstual Indonesia, 2024)
This study investigates the Mopat Asam ritual, a traditional practice of the Dayak Kebahant community in Kalimantan Barat, Indonesia. This ritual, conducted during pregnancy, aims to lift taboos and seek blessings for the mother and child. The research employs a qualitative approach, including in-depth interviews with key informants, document analysis, and direct observations in Desa Merah Arai. The study reveals the deep spiritual and social significance of the ritual, which aligns with various Christian principles. By analyzing the symbolic meanings and stages of Mopat Asam, the research explores its theological relevance and potential integration with Christian offering practices. The findings highlight how traditional values and religious practices can be harmonized, enriching the spiritual experiences of the Dayak Kebahant community. This integration fosters a deeper understanding of the sacredness of life and communal solidarity, bridging cultural traditions with Christian teachings.